1998
DOI: 10.1097/00004872-199816090-00014
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria predicts cardiovascular events and renal insufficiency in patients with essential hypertension

Abstract: This study suggests that hypertensive individuals with microalbuminuria manifest a greater incidence of cardiovascular events and a greater decline in renal function than do patients with normal UAE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
179
2
26

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(215 citation statements)
references
References 51 publications
8
179
2
26
Order By: Relevance
“…This finding is in agreement with the majority of previous reports and is consistent with the concept that UAE largely reflects the prevailing BP levels in hypertensive patients. 8,25 In contrast with some previous studies, 4,6 the classical risk factors for atherosclerosis were equally distributed among patients with and without microalbuminuria in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is in agreement with the majority of previous reports and is consistent with the concept that UAE largely reflects the prevailing BP levels in hypertensive patients. 8,25 In contrast with some previous studies, 4,6 the classical risk factors for atherosclerosis were equally distributed among patients with and without microalbuminuria in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Out of the patients with micro-or macroalbuminuria, 15.3% and 8.4% of the patients with normal AER had had myocardial infarction. This finding is quite expected keeping in mind that microalbuminuria is also a marker for damage not only in the kidney but also to the cardiovascular system (Bigazzi, Bianchi, Baldari, & Campese, 1998). There was, however, no significant difference in the prevalence of myocardial infarction in Type 2 diabetic patients with and without micro-or macroalbuminuria.…”
Section: Discussionsupporting
confidence: 54%
“…[1][2][3][4][5] There is substantial evidence to indicate that UAE in the microalbuminuria range is an independent risk factor for kidney and cardiovascular disease, and of mortality in type 1 and type 2 diabetes mellitus, [1][2][3][4][5][6] hypertensive subjects, non-diabetic subjects, as well as in the general population. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] However, recent studies conducted in type 2 diabetic patients revealed that even very low UAE rates, below those conventionally accepted as the lower limit to define microalbuminuria (o30 mg per 24 h), were also associated with increased mortality. 15 Similarly, in non-diabetic subjects, albuminuria of o30 mg day À1 was found associated with older age, male gender, smoking, obesity, elevated blood pressure, left ventricular hypertrophy, dyslipidaemia, hyperinsulinaemia, salt sensitivity, lack of nocturnal BP dipping [15][16][17][18][19] and increased risk of coronary heart disease and death 10,15,[20][21][22][23][24][25] (Table 1).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] However, recent studies conducted in type 2 diabetic patients revealed that even very low UAE rates, below those conventionally accepted as the lower limit to define microalbuminuria (o30 mg per 24 h), were also associated with increased mortality. 15 Similarly, in non-diabetic subjects, albuminuria of o30 mg day À1 was found associated with older age, male gender, smoking, obesity, elevated blood pressure, left ventricular hypertrophy, dyslipidaemia, hyperinsulinaemia, salt sensitivity, lack of nocturnal BP dipping [15][16][17][18][19] and increased risk of coronary heart disease and death 10,15,[20][21][22][23][24][25] (Table 1). In non-diabetic hypertensive individuals with left ventricular hypertrophy, the risk for cardiovascular morbidity and mortality increased continuously as the UAE increased.…”
mentioning
confidence: 99%